Big data, information asymmetry, and food supply chain management for resilience - Michelle Miller (Journal of Agriculture, Food Systems, and Community Development, 2021)
The Biden Administration is reviewing supply chains as part of its response to recent supply chain failures during COVID-19, and anticipated disruptions associated with climate change. This policy analysis discusses supply chain management, that is, the monitoring and continual improvement of materials flow and information flow to better manage risk. We are in an era of proprietary big data and digitized applications to make sense of it. Healthy food systems require policy to address unequal access to food systems data and information that occurs between businesses as well as between private businesses and government. Managing risk to a nation’s overall food system is an important government function that includes setting fair market rules and ensuring open information exchange in food supply chains. In this way, our government ensures equitable food and market access as new technologies and disruptions arise. This paper reviews these concepts considering current policy actions of the Biden Administration.